The Primary Leadership Style of School Leaders in Madinah City Boys Public Schools: An Investigation Using the Situational Leadership Theory - Alrajeh, Waleed Abdullah (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the primary leadership style for school leaders of boys' public schools in Medina based on the situational leadership theory, also it tested the relationship between the primary leadership style with leaders' qualification levels, years of experience, and qualification in educational leadership. This study targeted 217 school leaders from Medina boys' public schools who were randomly selected. Hersey and Blanchard (the Leader Effectiveness and Adaptability Description (LEAD-self)) instrument, which consisted of 12 situations and 4 responses to each situation, was adapted to the Saudi context and translated into Arabic and used in this study. Descriptive statistics were used in this study to obtain the primary leadership style for school leaders, and inferential statistics were used to obtain the relationship between the leaders' primary style with the academic qualification of leaders, the number of years of their experience in school leadership, and their qualification related to leadership by using the Chi-Square test.The study found that the primary leadership style for the study's sample is the supporting style, based on the results of 30 leaders. While the study did not find any significant relationship between the primary leadership style for school leaders, whether with their academic qualification, or their number of years of experience in the leadership of schools, or their qualification that based on leadership field. These findings were nearly similar to what other researchers found in different Saudi contexts. The study also found that more than 95% of the sample used 3 or 4 leadership styles, which is evidence of good flexibility in using leadership styles. This study recommended training of school leaders or candidates to lead schools on leadership theories in general and particularly on the situational leadership theory.
Keywords: situational leadership; school leaders; leadership style; boys’ public schools; Saudi Arabia; Madinah